Detectors in particle physics : a modern introduction - Viehauser, Georg; Weidberg, Tony (Boca Raton : CRC Press, 2024)
"This textbook provides an accessible yet comprehensive introduction to particle detectors. It emphasises the core physics principles, enabling a deeper understanding of the subject for further and more advanced studies. Case studies of the various applications of particle detectors are provided, particularly across medical physics. The primary audience is graduate students in particle or nuclear physics, in addition to advanced undergraduate students in physics. Particle detectors have a very broad range of applications, so this will also be a useful guide for more experienced particle physics researchers in software and analysis who wish to gain a good understanding of detector physics. Particle detectors are widely used outside of particle physics (such as astrophysicists using particle detectors on satellite missions), making this a valuable reference for interdisciplinary readers"--
Includes bibliographical references (page 307-334) and index.
The primary audience is graduate students in particle or nuclear physics, in addition to advanced undergraduate students in physics.
Keywords: Nuclear counters; Particles (Nuclear physics)